Learning Dynamics and Support for Economic Reforms : Why Good News Can Be Bad - van Wijnbergen, Sweder; Willems, Tim (World Bank Group, Washington, DC, 2014)
Support for economic reforms has often shown puzzling dynamics: many reforms that began successfully lost public support. This paper shows that learning dynamics can rationalize this paradox because the process of revealing reform outcomes is an example of sampling without replacement. This concept challenges the conventional wisdom that one should begin by revealing reform winners. It may also lead to situations in which reforms that enjoy both ex ante and ex post majority support will still not come to completion. The framework can be used to explain why gradual reforms worked well in China (where successes in Special Economic Zones facilitated further reform), whereas this was much less the case for Latin American and Central and Eastern European countries.